2015
DOI: 10.1007/s10803-015-2504-8
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Improve Social Skills in Young Adults with Autism Spectrum Disorder: The UCLA PEERS® Program

Abstract: Research suggests that impaired social skills are often the most significant challenge for those with autism spectrum disorder (ASD), yet few evidence-based social skills interventions exist for adults on the spectrum. This replication trial tested the effectiveness of PEERS, a caregiver-assisted social skills program for high-functioning young adults with ASD. Using a randomized controlled design, 22 young adults 18-24 years of age were randomly assigned to a treatment (n = 12) or delayed treatment control (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
144
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 49 publications
14
144
2
1
Order By: Relevance
“…It was also shown to have a positive impact on empathy and loneliness among this population. Although these findings were recently replicated within the site of development at UCLA (Laugeson, Gantman, Kapp, Orenski, & Ellingsen 2015), they have not yet been independently replicated outside of that site. Additionally, the data from both the original study and the replication were comprised of small sample sizes ( N = 17, N = 22, respectively).…”
Section: The Peers® Interventionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was also shown to have a positive impact on empathy and loneliness among this population. Although these findings were recently replicated within the site of development at UCLA (Laugeson, Gantman, Kapp, Orenski, & Ellingsen 2015), they have not yet been independently replicated outside of that site. Additionally, the data from both the original study and the replication were comprised of small sample sizes ( N = 17, N = 22, respectively).…”
Section: The Peers® Interventionmentioning
confidence: 97%
“…Additionally, the data from both the original study and the replication were comprised of small sample sizes ( N = 17, N = 22, respectively). Furthermore, both Gantman et al (2012) and Laugeson et al (2015) utilized the Autism Quotient (Baron-Cohen, Wheelwright, Skinner, Martin, & Clubley 2001) and a community diagnosis of ASD to confirm the diagnostic status of their participants, rather than employing a gold standard assessment measure.…”
Section: The Peers® Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific goals of the program include conversation skills, finding common interests with others, using humor, learning how to begin and end a conversation, being a good host at get-togethers, establishing how to handle disagreements, handling rejection, and etiquette. Researchers have shown that using this 16-week training program has resulted in positive outcomes in overall social skills, frequency of social engagement, and social skills knowledge in adolescents and young adults with ASD [41]. Another similar approach, presented by Tse and colleagues [42], has also demonstrated effectiveness in improving social skills in adolescents with ASD.…”
Section: Navigating Social and Romantic Relationshipsmentioning
confidence: 95%
“…For example, employees may need to request help from others when they run out of necessary materials, receive unclear instructions or feedback, or have finished their work. Although a small but growing number of studies have focused on interventions to improve social skills of adults with ASD, none has focused exclusively on those related to interactions on the job (e.g., Alexander, Dummer, Smeltzer, & Denton, 2011;Davis, Boon, Cihak, & Fore, 2010;Dotson, Leaf, Sheldon, & Sherman, 2010;Laugeson, Gantman, Kapp, Orenski, & Ellingsen, 2015).…”
mentioning
confidence: 99%